2021
DOI: 10.1111/ped.14582
|View full text |Cite
|
Sign up to set email alerts
|

False‐positive results in SARS‐CoV‐2 antigen test with rhinovirus‐A infection

Abstract: Fig. S1. Number of third-generation cephalosporin-susceptible and resistant pneumococcal meningitis cases. Susceptible: third-generation cephalosporin-susceptible; resistant: third-generation cephalosporin-resistant; PCV7 was introduced in 2010, and PCV13 was introduced 2013. The patients have been decreasing since introduction of vaccination.Table S1. Characteristics of patients infected with third-generation cephalosporin-susceptible and third-generation cephalosporin-resistant pneumococcal isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…One study reported three pediatric false-positive cases with the rapid antigen test Espline SARS-CoV-2 (Fujirebio, Tokyo, Japan) with rhinovirus infections. In these cases, film array revealed HRV/enterovirus infections, and human rhinovirus typeA was confirmed by RT-PCR with sequencing [5]. Another study reported three pediatric patients tested false positive for the same rapid antigen test and were later found to have had rhinovirus infections [4].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…One study reported three pediatric false-positive cases with the rapid antigen test Espline SARS-CoV-2 (Fujirebio, Tokyo, Japan) with rhinovirus infections. In these cases, film array revealed HRV/enterovirus infections, and human rhinovirus typeA was confirmed by RT-PCR with sequencing [5]. Another study reported three pediatric patients tested false positive for the same rapid antigen test and were later found to have had rhinovirus infections [4].…”
Section: Discussionmentioning
confidence: 89%
“…While they are convenient, false-positive results with RATs have been reported [4][5][6]. False-positive RATs results cause unnecessary isolation and increase in the burden of medical staff in facilities [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it did not include patients who were confirmed to be negative for SARS-CoV-2 by RT-PCR. Some antigen tests have been reported to show false positives [ 20 , 21 ], and their likelihood may be influenced by shortened judgment times; however, this issue was not evaluated in this study. Further, we could not compare the specificities of QuickNavi™-COVID19 Ag and the DIA evaluated.…”
Section: Discussionmentioning
confidence: 99%